Lifestyles, arterial aging, and its relationship with the intestinal and oral microbiota (MIVAS III study): a research protocol for a cross-sectional multicenter study - Lugones-Sánchez, Cristina; Santos-Mínguez, Sandra; Salvado, Rita; González-Sánchez, Susana; Tamayo-Morales, Olaya; Hoya-González, Amaya; Ramírez-Manent, José I.; Magallón-Botaya, Rosa; Quesada-Rico, José A.; Garcia-Cubillas, Miriam D.; Rodríguez-Sánchez, Emiliano; Gómez-Marcos, Manuel A.; et al. (Frontiers in Public Health, 2023)
Background: The microbiota is emerging as a new element in the pathophysiology of many diseases, including cardiometabolic diseases, and lifestyles probably cause the greatest variation in the composition of the human microbiome. The main objectives of the study are to analyze the association of lifestyles (diet, physical activity, tobacco and alcohol) with gut and oral microbiota and this with arterial aging and cognitive function in subjects without cardiovascular disease in the Iberian Peninsula. In addition, the mediating role of the microbiome in the relationship of lifestyles with arterial aging and cognitive function will be analyzed. Methods and analysis: The MIVAS III is a multicenter cross-sectional study that will take place in the Iberian Peninsula. One thousand subjects aged between 45 and 74 years without cardiovascular disease will be selected. The main variables are: Demographic, anthropometric and habits (tobacco and alcohol). Dietary pattern through a frequency consumption questionnaire (FFQ) and the Mediterranean Diet adherence questionnaire. Physical activity: International Physical Activity Questionnaire (IPAQ), Marshall Questionnaire and Accelerometer (Actigraph). Body composition (Inbody 230 impedance meter). Arterial aging: Medium intimate carotid thickness (Sonosite Micromax); Analysis (PWA) and pulse wave velocity (cf-PWV), (Sphygmocor System). Cardio Ankle Vascular Index (CAVI), ba-PWV and ankle brachial index (Vasera VS-2000®). Intestinal microbiota with the OMNIgene GUT kit (OMR -200) and analysis of the microbiome profile by massive sequencing of the 16S rRNA gene. Linear discriminant analysis (LDA) effect size (LEfSe) as well compositional analysis like ANCOM-BC will be used to identify differentially abundant taxa between groups. Further analyses will be performed on MicrobiomeAnalyst and R v.4.2.1 software from the rarefied samples, including α and β diversity, abundance profiling and clustering analysis. Discussion: Lifestyles act as modifiers of microbiota composition. However, there are no conclusive results demonstrating the mediating effect of the microbiota in the relationship between lifestyles and cardiovascular diseases. Understanding this relationship may facilitate the implementation of strategies for improving population health by modifying gut and oral microbiota. Trial registration: ClinicalTrials.gov Identifier: NCT04924907. Registered on April 21, 2021 (https://clinicaltrials.gov/ct2/show/NCT04924907)